Surface Modification Strategies for Improving the Cycling Performance of Ni‐Rich Cathode Materials - Weber, Daniel; Tripković, Đorđije; Kretschmer, Katja; Bianchini, Matteo; Brezesinski, Torsten (European journal of inorganic chemistry, 2020)
Ni‐rich layered lithium metal oxides are the cathode active materials of choice for high‐energy‐density Li‐ion batteries. While the high content of Ni is responsible for the excellent capacity, it is also the source of interfacial instability, limiting the material's lifetime due to a variety of correlated in‐ and extrinsic factors. Hence, reconciling the opposing trends of high Ni content and long‐term cycling stability by modifying the material's surface is one of the challenges in the field. Here, we review various studies on surface modification of Ni‐rich (≥ 80 %) layered cathode active materials in order to categorize current research efforts. Broadly, the three strategies of coating, surface doping and washing are discussed, each with their advantages and shortcomings. In conclusion, we highlight new directions of research that could bring Ni‐rich layered lithium metal oxide cathodes from the laboratory to the real world. This minireview compiles a selection of studies on the three surface modification strategies coating, surface doping, and washing of Ni‐rich (≥ 80 %) layered lithium metal oxides. Special focus is thereby given to methodology and practicality of those strategies with regard to current and future commercialization efforts of Ni‐rich cathode active materials.